Influence of sodium silicate, sodium aluminate, and Filicium decipiens charcoal on the conductivity of artificial zeolite / Henny Sudibyo ... [et al.] - Sudibyo, Henny; Agustin, Nindia; Karo Karo, Pulung; Ali, Suprihatin; Rohman, Fakhrony Sholahudin; Ali Bashah, Nur Alwani (Universiti Teknologi MARA Cawangan Pulau Pinang, 2023)
Fly ash-bottom ash of coal is a solid waste in many industries and electric power plants. One method to reduce that solid waste is by using it to produce artificial zeolite. The Filicium decipiens charcoal was added into artificial zeolite to increase its performance to adsorb water pollutants. The pumice stone is also used in this work as a source of silica. The manufacture of artificial zeolite was carried out by the hydrothermal method by optimizing the composition of sodium silicate from Lampung pumice silica, sodium aluminate from aluminum scrap, and charcoal of Filicium decipiens. From the characterization of the LCR meter, the optimum artificial zeolite obtains the conductivity value from 9.14×10-6 (S/cm) to 6.09×10-6 (S/cm), confirming that artificial zeolite is a semiconductor material. The highest conductivity of artificial zeolite will increase its performance as a catalyst and absorbent. The composition of the artificial zeolite after XRF characterization was aluminum, silica, phosphorus, potassium, calcium, titanium, vanadium, chromium, Mangan, and ferrite. From the XRD characterization result obtained, the dominant phase is Zeolite-A. SEM-EDX characterization results obtained a spherical and cylindrical microstructure of artificial.